Histopathological Study of Incidental Neoplastic Lesions in Autopsy Cases: A Retrospective Observational Study in a Tertiary Care Centre - Manjusha Dhawle; Shweta Watane; Abhishek Muley; Devanshi Shah; Ashwini Waso; Abhishikta Misra; Sushma Ramraje (Indian Journal of Forensic Medicine and Pathology, 2025)
Context: Autopsy remains an invaluable tool in the advancement of pathological knowledge, particularly through the identi𿿿cation of rare or incidental neoplastic and non neoplastic lesions that may otherwise remain undetected during life. Many such𿿿ndings are asymptomatic and cause no signi𿿿cant functional impairment. This study aims to underscore the signi𿿿cance of the incidental neoplastic lesions in pathological medicolegal autopsies. Aim: To determine the spectrum of histopathological𿿿ndings in neoplastic lesions identi𿿿ed during autopsy, whether or not they were related to the cause of death. Materials and Methods: A retrospective review of medicolegal autopsies conducted over a period of one year at a tertiary care center was performed. Histopathological examinations were carried out and the𿿿ndings were analyzed tidentify neoplastic lesions. Results: The present study consisted of a series of 303 autopsy cases from Department of Pathology in a tertiary care hospital conducted over a period of one year. The internal organs of total of 303 autopsies were sent for histopathological examination. Neoplastic lesions were identi𿿿ed in 4.95% ofcases. Conclusion: This study has added valuable insights to the repository of rare incidental neoplastic lesions. Autopsy studies remain crucial for uncovering clinically silent yet potentially signi𿿿cant pathological conditions, some of whichcould have impacted patient management if identi𿿿ed antemortem.